ANALISIS STRUKTURALISME DINAMIK PADA CERPEN “ROBOHNYA SURAU KAMI” KARYA A.A. NAVIS - Andini, Hollysa (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2021)
The purpose of this study was to determine the dynamic structuralism in the short story entitled "Robohnya Surau Kami" by A.A Navis. This type of research was library research or literature study. Data collection techniques used library techniques which were carried out through several stages, namely: collecting materials, reading, making notes, and analyzing the data. Data analysis that used in this study was descriptive analytic technique. The results of the study indicate that the dynamic structuralism of the short story was Robohnya Rumah Kami was interpreted as the collapse and fall of human faith in God which is marked by the character's decision to commit suicide as a way out of the problem which is basically forbidden by God.